Enhanced corrosion resistance of AM60 alloy with 2.0Ca via thermal oxidation and carbonization under an O₂/CO₂ atmosphere - S.Y. Liu; K. Tang; G.J. Liu; Z.H. Liu; X.Y. Lang; Y.F. Zhu; Q. Jiang (Journal of Materials Research and Technology)
Magnesium and its alloys have the advantages of high specific strength and specific stiffness, excellent thermal conductivity and vibration damping performance. However, due to their low corrosion potential and loose corrosion product film, the corrosion resistance of Mg alloys is poor, which seriously limits their utilization scope. In this paper, the corrosion resistance (CR) of AM60 alloy is investigated by adding 2.0 wt% Ca with subsequent thermal oxidation and Carbonation (TOC) at 400 °C for 15 h with different O₂/CO₂ ratios. Electrochemical impedance spectra and cross-sectional corrosion analysis reveal that the CR is much improved with the optimal O₂/CO₂ ratio of 1:3. This enhancement is attributed to the formation of a high-quality dual-layer protective structure, consisting of an outer MgCO₃/CaCO₃ composite layer and an inner MgO/CaO/Al₂O₃ composite layer. This protective film effectively mitigates micro-galvanic corrosion and provides resistance against Cl⁻ attack, contributing to the alloy's superior corrosion performance.